How ready are we? Measuring the Philippines' readiness for digital trade integration with the Asia-Pacific - Francis Mark A. Quimba; Sylwyn C. Calizo; Jean Clarisse T. Carlos; Jose Ramon G. Albert (Philippine Institute for Development Studies (PIDS), 2021)
This study assessed the Philippines' readiness for regional digital trade integration with the Asia-Pacific by using the Regional Digital Trade Integration Index (RDTII) framework to provide an analytical overview of the Philippines' digital trade policy and regulatory environment. Using the RDTII framework, the Philippines reported an overall RDTII score of 0.342 in 2020, which rates the country as having a slightly restrictive digital trade environment. In the same year, the Philippines performed best in three pillars: pillar 1 (tariffs and trade defense measures), pillar 6 (cross-border data policies), and pillar 8 (intermediary liability and content access). All of these three pillars scored less than 0.200, thus, indicating a nonrestrictive policy and regulatory environment. In contrast, the Philippines performed worst in three pillars: pillar 2 (public procurement), pillar 3 (foreign direct investment), and, pillar 5 (telecommunications infrastructure and competition). These three pillars reported a score of above 0.610, characterized by having a strongly restrictive policy and regulatory environment. Meanwhile, the Philippines was found to be slightly restrictive in intellectual property rights (pillar 4), domestic policies on the use of data (pillar 7), quantitative trade restrictions (pillar 9), standards (pillar 10), and online sales and transactions (pillar 11), which all received a score ranging from 0.210-0.400. This study finds that the Philippines generally has an open policy environment for digital trade, which suggests that it is ready for digital trade integration with the region. However, the proper implementation of some of these policies has not been fully achieved, and this could be a great obstacle or challenge to regional integration.
Keywords: 330